Case Report: Exome Sequencing Reveals LRBA Deficiency in a Patient With End-Stage Renal Disease - Taylan, Christina; Wenzel, Andrea; Erger, Florian; Göbel, Heike; Weber, Lutz T.; Beck, Bodo B. (Frontiers in Pediatrics, 2020)
Background: Lipopolysaccharide-responsive and beige-like anchor protein (LRBA) deficiency is characterized by autoimmunity, chronic diarrhea, and immunodeficiency. To date, no major renal disease or end-stage renal disease (ESRD) have been reported in association with LRBA deficiency. Minor renal manifestations have been found in a few patients, but kidney disease has not been systematically studied and may remain underdiagnosed in this highly variable entity. Results: At the age of 15 months the today 26-year-old male patient presented with pancytopenia, enteropathy, hypogammaglobulinemia, and failure to thrive. Chronic kidney disease was diagnosed at the age of six, and progressed to ESRD. The patient underwent cadaveric kidney transplantation at the age of 13 years. Bronchiolitis obliterans, post-transplant lymphoproliferative disease (PTLD) and chronic rejection complicated the post-transplant management. For graft loss, hemodialysis was reinstituted at the age of 16 years. After negative results of different targeted sequencing strategies, we identified a homozygous stop mutation c. (p.Q1010*) in the LRBA gene as the cause of his disorder by WES sequencing 21 years after the patient´s initial presentation. Conclusions: This first description of ESRD associated with LRBA deficiency broadens the spectrum of this disease entity. The molecular diagnosis in rare diseases like LRBA deficiency allows us to differentiate complications of medical treatment and procedures from manifestations of primary disease. Most importantly, it allows causative treatment.